Influence of combined posterior and medial-lateral mid-air trunk perturbations on knee biomechanics during single-leg landing - Song, Yu; Su, Wanyan; Gu, Yu; Malik, Nawfal; Nguyen, Thanh; Jordan, Anne; Savala, Elijah; Dai, Boyi (Frontiers in Sports and Active Living, 2025)
ObjectivesTo determine the effect of combined posterior and medial-lateral mid-air trunk perturbation on biomechanical variables associated with ACL loading during single-leg landings.DesignControlled laboratory investigation with a repeated-measures design.MethodThirty-seven injury-free reactional athletes performed double-leg jump and single-leg landing tasks under three mid-air trunk pulling perturbation conditions (posterior-lateral, posterior-medial, and no perturbation relative to the landing leg). Kinematic and ground reaction force (GRF) data were collected. Jump height, trunk flexion and lateral bending angles, and knee angles and moments during landing were calculated. Paired t-tests were performed to assess perturbation consistencies, while one-by-three repeated-measures ANOVAs were applied to other variables (α = 0.05).ResultsNo significant differences were observed in perturbation duration, timing, and jump height (p ≥ 0.276). Posterior-lateral perturbation demonstrated the greatest trunk lateral bending angles, knee flexion angle at initial ground contact (IC), peak knee abduction/internal rotation angles, peak posterior GRF, and peak knee adduction moments during landing compared to other conditions (p ≤ 0.004). Posterior-medial perturbation showed the smallest trunk flexion angles and knee flexion angles among all conditions (p ≤ 0.035), while greater peak posterior GRF and knee extension moments compared to no perturbation (p < 0.001).ConclusionsPosterior-lateral perturbation resulted in increased trunk lateral bending, leading to increased ACL loading variables in the frontal plane during single-leg landing. Additionally, posterior-medial perturbation primarily increased sagittal plane ACL loading variables. These findings help understand indirect-contact ACL injury mechanisms and highlight the importance of optimizing trunk control strategies in injury prevention.